The impact of demographic, clinical, and treatment factors on overall survival in ovarian carcinosarcomas: a National Cancer Database study - Chang, Amber; Surendra, Akaash; Hsia, Beau; Patel, Khilen; Thirumalareddy, Joseph; Tauseef, Abubakar (Frontiers in Oncology, 2025)
ObjectiveOvarian carcinosarcoma is a rare and highly aggressive biphasic neoplasm, accounting for less than 1% of ovarian malignancies. This study utilizes the National Cancer Database (NCDB) to examine the impact of demographics, clinical presentation, and treatment on the overall survival of patients diagnosed with ovarian carcinosarcoma.MethodsA cohort of 420 patients diagnosed with ovarian carcinosarcoma was identified in the NCDB from 2004 to 2020. Patient characteristics and management strategies were analyzed using Kaplan-Meier survival curves, log-rank tests, and multivariable Cox proportional hazard models to determine significance.ResultsAdvanced cancer stage was associated with increased mortality risk, as all stage comparisons yielded significant results, ranging from a nearly two-fold increase in risk comparing Stage I and Stage II cancers (HR: 1.96; 95% CI: 1.13 − 3.40; p = 0.017) to over a four-fold increase in Stage I vs. Stage IV hazard ratios (HR: 4.27; 95% CI: 2.64−6.90; p < 0.001). Likewise, increasing Charlson-Deyo comorbidity scores exhibited a trend towards higher mortality, although only the comparison of score 0 to scores ≥ 3 was statistically significant (HR: 6.70; 95% CI: 2.06−21.80; p = 0.002). Furthermore, only select comparisons within different income classes and educational attainment reached statistical significance. Treatment modalities were found to have inconsistent impacts on survival, as primary radiation therapy was associated with unfavorable survival outcomes (HR: 1.54; 95% CI: 1.00−2.37; p = 0.049), while chemotherapy significantly improved outcomes (HR: 0.40; 95% CI: 0.31−0.52; p < 0.001). When analyzed independently, surgical resection was not significantly associated with overall survival (HR: 0.95; 95% CI: 0.51−1.81; p = 0.887).ConclusionTumor staging, comorbidities, and certain treatment modalities were found to be significant predictive factors of ovarian carcinosarcoma survival. Comparisons between age, race, and insurance status were not significantly associated with overall survival.